Task sharing for managing common noncommunicable disease in a nurse led noncommunicable diseases clinic in peri-urban community of Chandigarh - Neha Kashyap; Kavita Kavita; Sushma Kumari Saini; Amarjeet Singh (Wolters Kluwer Medknow Publications, 2022)
Background: Nurse led noncommunicable diseases (NCD) clinic may address the significant shortage of human resource for health for managing common NCDs. The objective of this study is to assess the feasibility and effectiveness of nurse-led NCD clinic for identification, prevention, and management of common NCDs. Materials and Methods: A quasi experimental study was conducted at a Public Health Dispensary in periurban community of Northern India. Situational analysis and stakeholders' interview were done based on which the clinic was setup and run over a period of 2 months by registered nurses and nursing students to offer screening, health education and appropriate referral. The primary outcome of study was proportion of population screened, prevalence of common NCDs, risk factors modification, medication adherence, and patient satisfaction. Results: It was feasible to run a nurse led clinic in terms of availability of space, equipment to run the clinic and human resource. A total of 455 individuals aged ≥30 years were enrolled using the total enumeration sampling technique. There was a significant increase in screening rates from 0.29% to 3.7% in nurse-led NCD clinic. There was significant mean change in systolic blood pressure (18.75 ± 6.92 mm Hg), diastolic blood pressure (4.4 ± 3.71 mm Hg), random blood sugar (33.36 ± 38.49 mg/dl) Body Mass Index, and waist circumference (P < 0.01) among the population screened. Medication adherence significantly increased from 7.8% to 76.4% (P < 0.01) after 2 months of nurse-led NCD clinic. Conclusion: Task sharing for managing common NCDs in nurse-led NCD clinic was feasible and effective in increasing screening rates, medication adherence, and risk factors modification among studied population.